OS CONSELHOS DE GESTÃO PÚBLICA DE PONTA GROSSA E OS DESAFIOS À PARTICIPAÇÃO DA SOCIEDADE CIVIL - Martinazzo, Silvana de Lurdes (2016)
The aim of this article is to analyze the configuration of management councils in Ponta Grossa and the challenges concerning the participation of civil society, from the perspective of the government segment of the councils researched. The research refers to the period of 2014/2 and 2015/01 and it characterizes the organizational profile, the nature and constitution of the management councils as a possibility for a better understanding of the challenges. The research took the form of a quali-quantitative study case and its methodology included a literature review of the themes investigated, documentary research, in addition to a questionnaire applied to those linked to the 9 management councils investigated and, content analysis. The participants that agreed to answer the questionnaire were selected according to the criteria of their involvement with the consultant and deliberative government management councils. The research questionnaire was structured according to 4 axis: characterization of the research participants; the counselors´ performance, the functioning of the councils and civil society participation in the municipal management councils in Ponta Grossa. The theoretical framework was supported on reflections about State, Civil Society, Public Management and Management Councils; this framework provided the basis for the content analysis of the data generated in the field research. In addition to the existing management councils, the research identified their legal and organizational aspects and the perception of the weak participation of civil society in public management of public policies councils in Ponta Grossa through the evaluation of the government segment that participates in the process of management/management councils. At the same time, such government counselors point suggestions to face the challenges concerning the participation of civil society in Public Policies Management.